2018
DOI: 10.1037/spy0000114
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Mental Toughness Questionnaire 48 (MTQ48) in elite, amateur and nonathletes.

Abstract: The purpose of this study was to assess the psychometric properties of the Mental Toughness Questionnaire 48 (MTQ48) and assess the measurement invariance across elite, amateur and non-athletes. In total, 1096 participants aged between 18 and 58 years with a range of athletic experience -elite (n = 181), amateur (n = 577) and non-athletes (n = 338) -from various sports completed the MTQ48. The internal consistency of the scale was gauged through Omega for the total and relevant subscales. Factorial validity wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 42 publications
0
31
0
Order By: Relevance
“…The conceptual issue of why the abridged MT measures are unidimensional, whereas the parent MTQ-48 scale is multidimensional, is beyond the remit of this paper. However, it is important to note that despite sampling MTQ-48 subscales, the MTQ-18 best fitted a unidimensional model (Gucciardi et al, 2015; Birch et al, 2017; Vaughan et al, 2018) confirming the author’s assertion that the scale provides a global measure of MT.…”
Section: Discussionmentioning
confidence: 63%
“…The conceptual issue of why the abridged MT measures are unidimensional, whereas the parent MTQ-48 scale is multidimensional, is beyond the remit of this paper. However, it is important to note that despite sampling MTQ-48 subscales, the MTQ-18 best fitted a unidimensional model (Gucciardi et al, 2015; Birch et al, 2017; Vaughan et al, 2018) confirming the author’s assertion that the scale provides a global measure of MT.…”
Section: Discussionmentioning
confidence: 63%
“…Perry, Clough, Crust, Earle, and Nicholls [78] provided support for this solution. However, other researchers have reported large degrees of misspecification with samples comprised of elite, amateur and non-athletes [79]. Other studies have also failed to reproduce the 4C solution, and questioned its appropriateness [77,80].…”
Section: Plos Onementioning
confidence: 99%
“…Example items include "I can usually adapt myself to challenges that come my way" and "I don't usually give up under pressure". A recent study that tested the psychometric properties of the MTQ48 reported an overall omega value of .82 indicating high reliability (Vaughan, Hanna, & Breslin, 2017).…”
Section: Mental Toughness (Mt)mentioning
confidence: 99%